Associations Between Toll-like Receptor (TLR2, TLR3, TLR9) Gene Polymorphisms and Susceptibility to Gastrointestinal Protozoan Infections - Abbas , Abbas Ghafil; Aledhari , Marwa; Naser , Hassan Hachim (American Journal of Biology and Natural Sciences, 2026)
Infection with gastrointestinal protozoan like Cryptosporidium spp., Giardia lamblia, and Entamoeba histolytica are responsible for morbidity worldwide. our case-control study aimed to investigate the association between functional polymorphisms in recognition genes of innate immune, specifically Toll-like receptors TLR2 (rs5743708, Arg677Trp), TLR3 (rs3775291, A1234G), and TLR9 (rs5743836, C-1237T) and host susceptibility to Gastrointestinal Protozoan infections. The study enrolled 50 patients with confirmed protozoan infections microscopically (giardiasis: n=24; cryptosporidiosis: n=16; amoebiasis: n=10) and 50 matched healthy individuals. Allele frequency and genotype analyses, along with Hardy-Weinberg equilibrium testing in controls, were investigated. Results demonstrated significant disease-specific associations. Moreover, giardiasis risk (OR = 11.77, 95% CI: 2.13–65.06, p = 0.0012) was highly associated with TLR2 AA genotype. the TT genotype of TLR3, conferred increased susceptibility to cryptosporidiosis (OR = 6.07, 95% CI: 1.29–28.49, p = 0.0144). Additionally, the TLR9 GG genotype showed a notable association with amoebiasis (OR = 34.17, 95% CI: 4.55–256.47, p < 0.001and the AG genotype was associated with giardiasis (OR = 3.68, 95% CI: 1.05–12.92, p = 0.0352). This study underscores significance of variations of hosts genetic in infection outcomes, more investigation is needed into these variants as biomarkers for risk stratification and targets for immunomodulatory strategies. Findings of this study study confirm that these functional TLR polymorphisms are important host genetic factors affecting immune recognition which significantly predispose hosts to the protozoan infections regardless with the environmental exposure.